2016
DOI: 10.1161/circimaging.115.004229
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Volumes and Function by Three-Dimensional Echocardiography

Abstract: Because 3-dimensional echocardiography (3DE) does not imply any geometric assumption, it provides a more accurate 5,6 and reproducible 7 measurement of LA volumes than 2DE. Moreover, 3DE LA volume offers an incremental capability to predict cardiovascular events compared with 2DE. 8,9 Thus, 3DE has the potential to become the primary technique to assess LA size and function in clinical practice, pending the availability of robust reference values. At present, reference data of 3DE LA volumes and phasic functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(65 citation statements)
references
References 29 publications
1
59
0
5
Order By: Relevance
“…Recently, Authors have provided reference values for LA volumes and function by 3D echocardiography from a group of healthy subjects with a wide age range. 13 CMR is recognised as the gold standard technique to measure ventricular volumes and function; however, its specificity is extended also to left atrium through the use of the short-axis approach that is more reproducible than the biplane area-length method. 14 The strength of CMR is its high spatial resolution and definite myocardial border identification throughout the cardiac cycle.…”
Section: Multimodality Approach In La Assessmentmentioning
confidence: 99%
“…Recently, Authors have provided reference values for LA volumes and function by 3D echocardiography from a group of healthy subjects with a wide age range. 13 CMR is recognised as the gold standard technique to measure ventricular volumes and function; however, its specificity is extended also to left atrium through the use of the short-axis approach that is more reproducible than the biplane area-length method. 14 The strength of CMR is its high spatial resolution and definite myocardial border identification throughout the cardiac cycle.…”
Section: Multimodality Approach In La Assessmentmentioning
confidence: 99%
“…The main findings of this study are summarized as follows: (a) We established the reference values of LVLAVR at ventricular end-diastole and at ventricular end-systole; (b) significant age dependency of LVLAVR was observed in both sexes, showing that highest and lowest values were observed in the 3rd and ≥7th decades, respectively; (c) there was also gender dependency, reflecting lower values of LVLAVR at both ventricular end-diastole and ventricular end-systole in female subjects than in male subjects; (d) the contribution of echocardiography parameters was different for LVLAVR at ventricular end-diastole and LVLAVR at ventricular endsystole, characterizing that LV mass and LA functional parameters were correlated with LVLAVR at ventricular enddiastole, and LV mass and LV functional parameters were associated with LVLAVR at ventricular end-systole. 3DE provides accurate and reliable cardiac chamber volumes and their function in clinical practice (Badano et al, 2016;Muraru et al, 2013;Wu et al, 2013). It is generally accepted that aging significantly affects both LV and LA function (Fukuda et al, 2012;Kaku et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Age-and gender-related change in left ventricular (LV) and left atrial (LA) volumes has been reported in healthy subjects (Badano et al, 2016;Kaku et al, 2011). The left ventricle and left atrium are contiguous left heart chambers, and become a conduit during diastole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutoff values for LA total, passive and active EF, as well as LA longitudinal strain, were used from previously published studies. 22,23 The association between daytime, nighttime, and day-nighttime hypertension and different LA parameters was determined by univariate logistic regression analysis (odds ratio [OR] and 95% CI). The multivariate logistic regression analysis included different phenotypes of hypertension (daytime, nighttime, and day-nighttime hypertension), age, sex, BMI, 24-hour SBP, E/e', and LVMI.…”
Section: Discussionmentioning
confidence: 99%